ANALYSIS OF VARIABILITY PARAMETERS FOR MORPHOLOGICAL AND AGRONOMIC TRAITS IN GRAIN AMARANTH (AMARANTHUS SP) GENOTYPES - RASHMI YADAV; J. C. RANA; J. K. RANJAN (The Bioscan, 2014)
This study was aimed to evaluate genotypic variability and character association in grain amaranth genotypes for agronomically useful and yield contributing traits. The characters like leaf blade width, lateral spikelet length and grain yield per plant showed high GCV and PCV values. Genotypic coefficient of variation for different characters ranged from 11.60 to 42.73%. The highest GCV was recorded with grain yield per plant (42.73%). High heritability exhibited for all the characters studied ranged from 97.81 to 99.98%. The estimates of heritability were observed to be high in magnitude for days to 80 % maturity, days to 50 % flowering, leaf blade width, inflorescence length and plant height. At genotypic level, seed yield per plant showed highly significant positive correlation with days to 80% maturity (rg = 0.696) and plant height (rg = 0.403) and significant positive correlation with days to 50% flowering (rg = 0.338). Inflorescence length had significant positive correlation with lateral spikelet length.